Resurrection of the Family Grateloupiaceae Emend. (Halymeniales, Rhodophyta) Based on a Multigene Phylogeny and Comparative Reproductive Morphology - Kim, Su Yeon; Lee, Hyung Woo; Yang, Eun Chan; Boo, Sung Min; Lopez-Bautista, Juan; Fredericq, Suzanne; D’Archino, Roberta; Yoon, Hwan Su; Kim, Myung Sook (Frontiers in Ecology and Evolution, 2021)
The marine red algal order Halymeniales currently includes two families, the Halymeniaceae and Tsengiaceae, and consist of 38 genera and about 358 species. Phylogenetic analyses on specific taxa of the order are common, but not comprehensive, leaving the many intra-ordinal relationships within the Halymeniales unresolved. To reassess the phylogeny of the Halymeniales, we conducted extensive phylogenetic analyses based on 207 rbcL sequences and multigene analyses (rbcL, psaA, psbA, cox1, and LSU) using 47 taxa from the order. The combined data set fully supports the monophyly of the Grateloupia sensu lato clade. Phylogenetic assessment of the reproductive structures in the order using the type of auxiliary cell ampullae, pericarp origin, and tetrasporangial development characters, supports a Grateloupia sensu lato clade distinct from the Halymeniaceae exemplified by the generitype Halymenia. As a result, we propose to reinstate the family Grateloupiaceae Schmitz based on the Grateloupia sensu lato clade and including Grateloupia and eight other genera: Dermocorynus, Mariaramirezia, Neorubra, Pachymeniopsis, Kintokiocolax, Phyllymenia, Prionitis, and Yonagunia. The emended Grateloupiaceae is distinguished from the Halymeniaceae by the following three characteristics; (i) simple unbranched and unilateral type of auxiliary cell ampullae, (ii) pericarp formed densely by the fusion of secondary medullary filaments from subcortical cells and lateral ampullary filaments from a fusion cell complex, (iii) tetrasporangia originating laterally from the outer cortex. The Halymeniales comprises the monophyletic Grateloupiaceae, Halymeniaceae sensu lato (which requires further study), and the Tsengiaceae.